CONTEMPORARY THERAPEUTIC APPROACHES TO DRY EYE SYNDROME: A SYSTEMATIC REVIEW OF CLINICAL EVIDENCE WITH IMPLICATIONS FOR OCULAR HEALTH AND QUALITY OF LIFE - Justyna Niebylecka; Natalia Glanc; Julia Kular; Oliwia Malec; Izabella Michalska; Mateusz Myśliwiec; Tytus Tyralik; Maciej Karwat; Dominik Sendecki; Grzegorz Zalewski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Dry Eye Syndrome (DES), or Dry Eye Disease (DED), is a common, multifactorial condition affecting the tear film and ocular surface. It causes symptoms such as discomfort, visual disturbances, and inflammation. Treatments range from artificial tears and anti-inflammatory drops to newer approaches like light-based therapies, electrotherapy, and biological tear substitutes. Objective: This systematic review evaluates current pharmacological and non-pharmacological treatments for DES, focusing on clinical effectiveness, safety, and evidence quality - particularly from randomized controlled trials. Methods: A comprehensive search was performed in major databases for studies published between January 2010 and April 2025. Included studies were in English, involved human subjects with DES, and assessed specific treatments with measurable outcomes (e.g., tear production, symptom severity). Eligible studies included randomized controlled trials, observational studies, and systematic reviews with meta-analyses. Two reviewers independently screened and selected studies, data were extracted and analyzed descriptively due to heterogeneity. Results: A wide range of therapies were identified. Artificial tears, especially preservative-free and hyaluronic acid-based, consistently improved symptoms and tear stability. Cyclosporine A showed moderate anti-inflammatory effects. Biological tear substitutes, like autologous serum and platelet-rich plasma, benefited severe cases. Non-pharmacological treatments such as intense pulsed light (IPL), low-level light therapy, electrotherapy, and acupuncture improved outcomes in meibomian gland dysfunction. Omega-3 and curcumin supplements had mixed but promising effects. Conclusions: DES management should be personalized and multimodal. Although many treatments show benefits, variations in study designs limit comparability. More standardized, high-quality research is needed to guide evidence-based care.